Development of a validated patient satisfaction survey for HIV clinic attendees. (March 2013) - Land, L; Sizmur, S; Harding, J; Ross, JDC
Patients are becoming more actively involved in decisions about their care and have greater influence to change and improve the quality of services by reporting their experiences. A recent systematic review failed to reveal a method of measuring HIV patient satisfaction that reflects their experience of contemporary treatment and care. The aim of this study was to design a specific HIV patient satisfaction questionnaire that can be used as a patient reported outcome measure. Key themes in the systematic review were identified and used as a topic guide for focus group discussion to confirm their relevance and importance. HIV patients were also interviewed about their motivation to complete a questionnaire. The data from the focus groups and interviews were used to develop an initial questionnaire and cognitive testing was used to provide face validity for the questionnaire design, layout and wording. A revised version was used in a pilot study of 80 respondents, which demonstrated that the questionnaire's completion rate and content validity were high.